Candida albicans Pma1p Contributes to Growth, pH Homeostasis, and Hyphal Formation - Rane, Hallie S.; Hayek, Summer R.; Frye, Jillian E.; Abeyta, Esteban L.; Bernardo, Stella M.; Parra, Karlett J.; Lee, Samuel A. (Frontiers in Microbiology, 2019)
Candida albicans occupies diverse ecological niches within the host and must tolerate a wide range of environmental pH. The plasma membrane H+-ATPase Pma1p is the major regulator of cytosolic pH in fungi. Pma1p extrudes protons from the cytosol to maintain neutral-to-alkaline pH and is a potential drug target due to its essentiality and fungal specificity. We characterized mutants in which one allele of PMA1 has been deleted and the other truncated by 18 to 38 amino acids. Increasing C-terminal truncation caused corresponding decreases in plasma membrane ATPase-specific activity and cytosolic pH. Pma1p is regulated by glucose: glucose rapidly activates the ATPase, causing a sharp increase in cytosolic pH. Increasing Pma1p truncation severely impaired this glucose response. Pma1p truncation also altered cation responses, disrupted vacuolar morphology and pH, and reduced filamentation competence. Early studies of cytosolic pH and filamentation have described a rapid, transient alkalinization of the cytosol preceding germ tube formation; Pma1p has been proposed as a regulator of this process. We find Pma1p plays a role in the establishment of cell polarity, and distribution of Pma1p is nonhomogenous in emerging hyphae. These findings suggest a role of PMA1 in cytosolic alkalinization and in the specialized form of polarized growth that is filamentation.